Myometrial Cystic Formation after Local Methotrexate Application into Cornual Gestational Sac: A Case Report of an Unexpected Complication. (9th July 2011) - Ozkan, Zehra Sema; Kumbak, Banu; Sapmaz, Ekrem; Simsek, Mehmet
Abstract : Cornual pregnancy is a rare type of ectopic pregnancy, and diverse therapeutic options exist for the management. Medical treatment despite high initial beta HCG values is not thought to be safe. We reported a 39-year-old woman with an initial beta HCG value of 22000 mIU/mL and diagnosed of a cornual pregnancy. Patient was managed successfully with the administration of combined systemic and ultrasonographically guided local injection of methotrexate into the gestational sac. During followup with serial beta hcg measurements, 27 × 20  mm cystic area in myometrium has been detected. Beta hcg <1 mIU/mL value was reached three months later, and this cystic area resolved spontaneously. Systemic methotrexate administration combined with ultrasound-guided local methotrexate injection into the gestational sac might be considered as the first-line treatment in the management of hemodynamically stable patients having cornual pregnancy even with high beta HCG values and risk of myometrial cystic formation.